Multiple Injection of Human Wharton’s Jelly Mesenchymal Stem Cells Ameliorate Spermatogenic Cells on Physiological Aging Male Rats - alif imam fitrianto (Stem Cell Research and Development Center, Universitas Airlangga, 2019)
Recently, the most common therapy on men who suffered fertility decline due to aging was testosterone replacement, but now it is known that this therapy has a long-term risk of damage to the cardiovascular system and prostate. Stem cells are an alternative therapy that has a potency to improve the fertility of aging men that less causing side effects. The aim of this study was to evaluate the injection of Human Wharton’s Jelly Mesenchymal Stem Cells (hWJ-MSC) in physiologic aging male rats on spermatogenic cells. This study used 3 young male rats (8-12 weeks) and 6 physiological aging rats (22-24 months) which divided into 3 groups, the young rat group did not give any treatment, physiological aging male rats received NaCl (0.9%) 0.4 mL, and physiological aging male rats received 1x106 cells/kg BW of hWJ-MSCs. The observations were performed on histological analysis. The results indicate that the hWJ-MSCs injections increased the number of spermatogonia and Leydig cells significantly (P<0.05), and improve the tubules circumference and interstitial area significantly (P<0.05). The mechanism of spermatogenic cells repairs suspected due to various bioactive molecules that secreted by hWJ-MSCs which can affect the surrounding cells.